Optimization of bacteriocin-like inhibitory substance production by Pediococcus acidilactici Kp10 for use as food preservative - Abbasiliasi, Sahar (2014)
The present study was carried out in view of the considerable interest in the search for safe, food-grade preservatives of biological origin. Towards this objective, lactic acid bacteria (LAB) were isolated from a number of milk by-products and fermented cocoa beans. The isolates were then screened for their ability in the production of bacteriocin-like inhibitory substance (BLIS). The physicochemical cell surface and adhesive properties of the bacterial strains were assessed using phenol, solvents, congo-red and n-hexadecane. The culture conditions for the production of BLIS by the isolated strain in the shake flask culture were optimized by the response surface methodology (RSM) and the artificial neural network (ANN). The influence of three independent variables (temperature, inoculum size and agitation speed) were examined in the optimization of culture conditions for the production of BLIS. The polymer–salt aqueous two phase system (ATPS) comprising of polyethylene–glycol (PEG) with sodium citrate was developed for direct recovery of BLIS. In this system, the influence of several parameters such as phase composition, tie-line length (TLL),volume ratio (VR), crude sample loading, pH and the addition of sodium chloride (NaCl) on the partitioning behaviour of BLIS was also investigated. Finally,production of BLIS was conducted in stirred tank bioreactor for the identification of parameters in the scaling up. Data obtained were also analysed by mathematical models to study the kinetics of cell growth, lactose consumption and BLIS production. A total of 222 LAB strains were isolated from fresh curd, dried curd, and ghara (a traditional flavor enhancer prepared from whey), and fermented cocoa beans. Eleven LAB isolates which have substantial antimicrobial properties were identified as Lactococcus lactis, Lactobacillus plantarum, and Pediococcus acidilactici by biochemical methods and 16S rRNA gene sequencing. Cell-free supernatant of P.acidilactici Kp10 exhibited the highest inhibition to Listeria monocytogenes, an important pathogen in the food industry. BLIS produced by P. acidilactici Kp10 was determined to be proteinaceous in nature and active over a wide range of pH. In this respect, P. acidilactici Kp10 was selected for the development of a fementation process for BLIS production. P. acidilactici Kp10 was found to be catalase-negative,able to produce β-galactosidase, resistant to bile salts (0.3%) and acidic conditions (pH 3), and susceptible to most antibiotics. P. acidilactici Kp10 also displayed good tolerance to the gastrointestinal environment, adhesion ability to intestinal mucosa and capable to inhibit pathogens. The ANN-predicted levels of agitation speed, inoculum size, and temperature for optimal BLIS production by P. acidilactici Kp10 in shake flask fermentation were 120 rpm, 3% and 28.5 oC respectively. On the other hand, the predicted levels for the same variables using RSM were 126 rpm, 5.5% and 28.5 oC respectively. The predicted BLIS activity (5,262.64 AU/mL) obtained by the ANN was comparable with that obtained by the RSM (6,311.5 AU/ mL). However, The observed BLIS activity at the predicted optimum levels of the tested variables by RSM and ANN was 5,118.5 AU/ mL. ANN was considered to be a preferred optimization tool than RSM as the activity predicted by ANN was closer to the observed values at all experimental levels of three variables. The overall production of BLIS in optimized fermentation was enhanced at least by 30 times in comparison to those obtained in non-optimized fermentation. Under optimum conditions of the ATPS, purification of BLIS was achieved at 26.5% PEG (8,000)/ 11% citrate system comprising of TLL at 46.38% (w/w), VR of 1.8,without the addition of NaCl and 1.8% crude load at pH 7.0. BLIS from P.acidilactici Kp10 was partially purified by the ATPS up to 8.43-fold with a yield of 81.18%. BLIS production by P. acidilacti Kp10 in stirred tank bioreactor was a growth associated process where the production was greatly influenced by the aeration and agitation conditions of the bioreactor and the level of dissolved oxygen in the culture. Results from this study demonstrated that P. acidilactici Kp10 could be used as the potential probiotic for applications in food industry. Efficient large scale production of BLIS by P. acidilactici Kp10 could be performed using stirred tank bioreactor with controlled cultivation at optimal conditions. BLIS from P. acidilactici Kp10 could be efficiently extracted and purified for commercial application using ATPS, which is a more economical method.